Cerebral glucose metabolism and cognitive impairment in tremor-dominant and akinetic-rigid subtypes of Parkinson’s disease - I. V. Miliukhina; Yu. G. Khomenko; E. V. Gracheva; G. V. Kataeva; E. A. Gromova (Неврология, нейропсихиатрия, психосоматика, 2020)
Parkinson’s disease (PD) is a disease characterized by marked phenotypic heterogeneity. The akinetic-rigid (AR) and tremor-dominant (TD) types of PD differ not only in motor manifestations, but also in the severity of non-motor symptoms, including cognitive impairment (CI). It is the PD heterogeneity study that can achieve the task of creating a modern personalized therapy for this disease.Objective: to study the characteristics of cerebral glucose metabolism in CI in patients with AR and TD PD.Patients and methods. Examinations were made in 69 patients with PD (the TD and AR subtypes were in 23 and 46 patients, respectively). Their cognitive status was assessed using the Mini-mental State Examination, the Montreal Cognitive Assessment, the Frontal Assessment Battery, and the Clock Drawing Test. 18F-fluorodeoxyglucose positron emission tomography was performed according to the standard procedure; glucose metabolism rate (GMR) was determined in different Brodmann areas (BA).Results and discussion. GMR in the frontal areas (right BA 6, 8, 9, 46 and left BA 46) was lower in the AR group that in the TD one (p< 0.05). The severity of CI in the AR group correlated with GMR in the parietal and posterior cingulate cortex (BA 7, 23, 26, 29, 30, and 31). The TD group showed correlations of the values of cognitive tests mainly with GMR in the frontal and anterior cingulate cortex (BA 6, 8–11, 24), and in the parietal (BA 7) and temporal cortices (BA 22). The only area, in which GMR correlated with cognitive performance in both groups, was BA 7.Conclusion. Two distinct patterns of GMR were identified in AR and TD within the general pattern of decreased cerebral glucose metabolism, which was specific for CI in PD. The findings may suggest that there are two different CI pathogenetic mechanisms associated with the clinical subtypes of PD.